Investigation on Reconstruction of Three-dimensional Temperature Field in a Biological Body with Finite Element Method (Journal of Fiber Bioengineering and Informatics, 2015)
The noninvasive detection and reconstruction of 3D temperature field in a biological body have receivedincreasing attention in bio-medical engineering field. Based on the classical Pennes bioheat transferequation, the heat transfer mathematical model fitting for breast tissue is founded in this paper.Meanwhile, using the large analysis software ANSYS, the modeling and simulating of heat transferin pork and intravital breast tissue are presented combining with Finite Element Method (FEM). Theresult shows, the 3D temperature field can be well reconstructed efficiently, which will play a positiverole in promoting many research field such as tumor thermotherapy, cryosurgery, cryo-preservation ofbiomaterial and so on.
Keywords: Finite Element Method (FEM); 3D Temperature Field; Biological Tissue; Bioheat Transfer